2019
DOI: 10.1093/beheco/arz054
|View full text |Cite
|
Sign up to set email alerts
|

Rate of intersexual interactions affects injury likelihood in Tasmanian devil contact networks

Abstract: Identifying the types of contacts that result in disease transmission is important for accurately modeling and predicting transmission dynamics and disease spread in wild populations. We investigated contacts within a population of adult Tasmanian devils (Sarcophilus harrisii) over a 6-month period and tested whether individual-level contact patterns were correlated with accumulation of bite wounds. Bite wounds are important in the spread of devil facial tumor disease, a clonal cancer cell line transmitted thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 69 publications
3
47
0
Order By: Relevance
“…The low rate of injurious contacts we recorded during active travel and at dens and carcasses is similar to direct observations of interactions recorded around carcasses [11] and potentially lower than rates of biting injury during mating interactions indicated by indirect methods-proximity-sensing radiocollars and new injuries recorded when these collared individuals are trapped [17]. It is the injurious mating interactions that are thought to contribute most to transmission [17]. Our study thus contributes new information towards building a holistic understanding of the frequency and context of social contacts between devils that are relevant to transmission of DFTD.…”
Section: Plos Onesupporting
confidence: 82%
See 3 more Smart Citations
“…The low rate of injurious contacts we recorded during active travel and at dens and carcasses is similar to direct observations of interactions recorded around carcasses [11] and potentially lower than rates of biting injury during mating interactions indicated by indirect methods-proximity-sensing radiocollars and new injuries recorded when these collared individuals are trapped [17]. It is the injurious mating interactions that are thought to contribute most to transmission [17]. Our study thus contributes new information towards building a holistic understanding of the frequency and context of social contacts between devils that are relevant to transmission of DFTD.…”
Section: Plos Onesupporting
confidence: 82%
“…Little is known about the ecology of wild devil dens but one study found that individuals use between one and ten dens and change dens every few days [19]. The low rate of injurious contacts we recorded during active travel and at dens and carcasses is similar to direct observations of interactions recorded around carcasses [11] and potentially lower than rates of biting injury during mating interactions indicated by indirect methods-proximity-sensing radiocollars and new injuries recorded when these collared individuals are trapped [17]. It is the injurious mating interactions that are thought to contribute most to transmission [17].…”
Section: Plos Onesupporting
confidence: 65%
See 2 more Smart Citations
“…disease ecology, emerging infectious disease, epidemiology, Tasmanian devil facial tumour disease, transmissible cancer season (Hamede, McCallum, & Jones, 2008;Hamede et al, 2013;Hamilton et al, 2019), DFTD transmission has been described as frequency-dependent and affects mostly sexually mature adult devils . The low DFTD prevalence in subadults might be attributed to the low number of bite wounds in this demographic group, (Hamede et al, 2013), an apparent extended latent period of DFTD ) and/or differences in immune function between subadults and adults (Cheng et al, 2017;Ujvari, Hamede, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%